2021
DOI: 10.3390/brainsci11060812
|View full text |Cite
|
Sign up to set email alerts
|

All-Trans Retinoic Acid Fosters the Multifarious U87MG Cell Line as a Model of Glioblastoma

Abstract: Glioblastoma multiforme (GBM) is a primary brain cancer of poor prognosis, with existing treatments remaining essentially palliative. Current GBM therapy fails due to rapid reappearance of the heterogeneous neoplasm, with models suggesting that the recurrent growth is from treatment-resistant glioblastoma stem-like cells (GSCs). Whether GSCs depend on survival/proliferative cues from their surrounding microenvironmental niche, particularly surrounding the leading edge after treatment remains unknown. Simulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Recently, we validated and deciphered the phenotypic nuances of the GBM cell line U87MG (ECACC 89081402; p53 wild-type; methylated MGMT promoter) [ 2 , 26 , 27 ]. Findings revealed that exposure to all-trans retinoic acid (ATRA) attenuated the expression of prominin-1 (CD133), a stem cell marker.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we validated and deciphered the phenotypic nuances of the GBM cell line U87MG (ECACC 89081402; p53 wild-type; methylated MGMT promoter) [ 2 , 26 , 27 ]. Findings revealed that exposure to all-trans retinoic acid (ATRA) attenuated the expression of prominin-1 (CD133), a stem cell marker.…”
Section: Introductionmentioning
confidence: 99%
“…Findings revealed that exposure to all-trans retinoic acid (ATRA) attenuated the expression of prominin-1 (CD133), a stem cell marker. Histochemical evidence highlighted the presence of prominin-1 in the cytoplasm but its absence in perinuclear space [ 26 ]. Conversely, the intercellular adhesion molecule-1 (ICAM-1; CD54), a chemotherapeutic targeting molecule, showed increased expression in response to ATRA [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Aze5-angiopep-2 nanoassemblies were then functionalized with A-COOP-K peptide for targeting of two glioblastoma cell models, namely, U-87-MG and U-138-MG glioblastoma cells. Both these cell lines have been utilized as models for examining glioblastoma cell interactions in previous studies. , Supramolecular nanofibrillar structures were formed that efficiently entrapped the chemotherapeutic drug doxorubicin (DOX) and the interactions of the drug entrapped nanoassemblies with glioblastoma cells were examined. Furthermore, three-dimensional spheroids of the cells were grown, and the internalization of the drug entrapped nanoassemblies was explored.…”
Section: Introductionmentioning
confidence: 99%